The use of amino acid formulas in the treatment of children with congenital epidermolysis bullosa - M. A. Kosareva; V. S. Nikonova; O. S. Orlova (Лечащий Врач)
Congenital epidermolysis bullosa is a group of rare (orphan) diseases characterized by disruption of intercellular connections in the epidermis or epidermal-dermal junction and leading to the formation of blisters on the skin and/or mucous membranes even with minor injury. In addition to the violation of the integrity of the skin and the need to care for it, in patients with congenital epidermolysis bullosa, there is a lesion of the gastrointestinal tract, and therefore, the nutrition of children with congenital epidermolysis bullosa is of particular attention. The presence of multiple non-healing erosions and large transdermal losses of protein, serous fluid, and sometimes blood, as well as increased heat transfer, increase the need for energy and macronutrients in patients with congenital epidermolysis bullosa. Daily energy needs correspond to 115-150% of the age norms of consumption, and even more with pronounced erosion. The protein requirements are 115-200% of the age norm, in liquid – 150-200 ml/kg. Also, patients with congenital epidermolysis bullosa need to replenish ω-3 fatty acids, additional subsidies of microelements (zinc, iron, etc.) and vitamins (D, C, A, B12, B6, etc.). In case of formula feeding patient with BE it is extremely important to select appropriate formula. The loss of barrier properties by skin and mucous membranes causes an excessive intake of antigens, incl. allergens. Violation of barriers can cause sensitization to cow's milk proteins, with the subsequent development of a clinically significant allergy. In this regard, amino acid formula should be used as baseline nutrition, which ensure the absorption of nutrients under conditions of significant inhibition of the digestive tract's digesting and absorption capacity, and also minimize the antigenic load. Thus, patients with congenital epidermolysis bullosa require constant monitoring and assessment of nutritional status, with the earliest possible initiation of adequate nutritional support. Effective maintenance therapy and nutritional correction can improve the quality of life of patients and compensate for the loss of vital macro- and micronutrients.